Towards resolving the purchasing power parity (PPP) 'Puzzle' in newly industrialized countries (NIC's). Issue 2 (17th February 2022) - De Villiers, David; Phiri, Andrew
ABSTRACT: The purchasing power parity (PPP) hypothesis represents one of the oldest existing economic doctrines and is plagued with empirical inconsistencies collectively labelled as 'puzzles'. Theory suggests that there exist several frictions to price movements that manifest themselves as nonlinear adjustment processes whilst traditional empirical methodologies for evaluating PPP are, however, inadequate in accounting for these phenomena. To close the gap between theory and empirical evidence, the fractional frequency flexible Fourier form (FFFFF) unit root test is used to capture asymmetries and approximate unknown structural breaks in the real exchange rate series for 14 newly industrialised countries (NIC's). Our study proposes a new binary search method to ease the computational burden and reduce the approximation errors in obtaining the optimal fractional frequencies used in the test. The main result of the study is that all NIC's real exchange rates are mean-reverting over the monthly periods of 1970:1–2018:12 once asymmetries and structural breaks are simultaneously accounted for although there exists heterogeneity in the different forms of asymmetries between the different NIC's. Policy implications of the study are discussed.